Activation of the transforming growth factor‐β/SMAD transcriptional pathway underlies a novel tumor‐promoting role of sulfatase 1 in hepatocellular carcinoma. Issue 4 (13th February 2015) - Dhanasekaran, Renumathy; Nakamura, Ikuo; Hu, Chunling; Chen, Gang; Oseini, Abdul M.; Seven, Elif Sezin; Miamen, Alexander G.; Moser, Catherine D.; Zhou, Wei; van Kuppevelt, Toin H.; van Deursen, Jan M.; Mounajjed, Taofic; et al.
Abstract : In vitro studies have proposed a tumor suppressor role for sulfatase 1 (SULF1) in hepatocellular carcinoma (HCC); however, high expression in human HCC has been associated with poor prognosis. The reason underlying this paradoxical observation remains to be explored. Using a transgenic (Tg) mouse model overexpressing Sulf1 (Sulf1‐Tg), we assessed the effects of SULF1 on the diethylnitrosamine model of liver carcinogenesis. Sulf1‐Tg mice show a higher incidence of large and multifocal tumors with diethylnitrosamine injection compared to wild‐type mice. Lung metastases were found in 75% of Sulf1‐Tg mice but not in wild‐type mice. Immunohistochemistry, immunoblotting, and reporter assays all show a significant activation of the transforming growth factor‐β (TGF‐β)/SMAD transcriptional pathway by SULF1 both in vitro and in vivo . This effect of SULF1 on the TGF‐β/SMAD pathway is functional; overexpression of SULF1 promotes TGF‐β‐induced gene expression and epithelial–mesenchymal transition and enhances cell migration/invasiveness. Mechanistic analyses demonstrate that inactivating mutation of the catalytic site of SULF1 impairs the above actions of SULF1 and diminishes the release of TGF‐β from the cell surface. We also show that SULF1 expression decreases the interaction between TGF‐β1 and its heparan sulfate proteoglycan sequestration receptor, TGFβR3. Finally, using gene expression from human HCCs, we show that patients with high SULF1 expression have poorer recurrence‐free survival (hazard ratio 4.1, 95% confidence interval 1.9‐8.3; P  = 0.002) compared to patients with low SULF1. We also found strong correlations of SULF1 expression with TGF‐β expression and with several TGF‐β‐related epithelial–mesenchymal transition genes in human HCC. Conclusion : Our study proposes a novel role of SULF1 in HCC tumor progression through augmentation of the TGF‐β pathway, thus defining SULF1 as a potential biomarker for tumor progression and a novel target for drug development for HCC. (Hepatology 2015;61:1269–1283)